Religion and the Representative Anecdote: Replacement and Revenge in AMC's "The Walking Dead" - Engstrom, Erika (Journal of media and religion, 2016)
The current study examines how the horror-based AMC television series The Walking Dead portrays religion in terms of a reframing of the role, if any, of faith in a higher power, and the portrayal of the faithful. The religious-themed discourse of this highly successful story about survivors of a zombie apocalypse as presented through dialogic and visual imagery serves as the text analyzed here; specifically, related episodes set in churches at two separate points in the series that combine to offer a metaphor of "structure" used to disassemble and reconstruct the role of religion. These episodes interlace religious themes to develop an overarching message that forms a representative anecdote of replacement in which the notion of "faith" becomes redefined.